The Role of Social Media as an Effort to Increase Participation of Novice Voters in Padangsambian Kaja Village in the 2024 Election - I Made Suidarma1; Ni Putu Mahera Nugrahayani (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
Indonesia is a country that upholds democracy by declaring that supreme sovereignty is in the hands of the people. General elections are an effort to implement a democratic system, of course by involving the role of the community. As time goes by, people who do not participate in elections can be seen in the emergence of the abstention phenomenon, so efforts are needed that can again increase voter participation, especially among first-time voters during the 2024 elections. Keeping up with the times, the role of social media has a big impact on the continuity of elections because it can be used as a media to reach the public in large numbers and more efficiently in time, place, and energy compared to using other media. Even political figures and government institutions have used social media to show their performance in cyberspace. This shows that social media plays a very important role and can be used as an effort to increase the participation of first-time voters, especially in Padangsambian Kaja Village in the 2024 general election.